Unlocking the Minds in the Lockdown: Pros and Cons of E-learning Implementation - Huma, Zilli; Baseer, Najma (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Nowadays our lives are dominated by technology. This paradigm shift has affected the academics considerably. On one hand, by granting wider access and promoting continuing education through digital platforms, technology has proven to be a great enabler for learning and as a teaching and learning approach has gained immense popularity in the recent years. On the contrary, the excessive use of technology has also met with criticism.1 E-learning has emerged as a useful strategy, which is utilized as an adjunct to on campus teaching and learning during the pre-pandemic times. However, in the current scenario, e-learning has overtaken the on campus teaching and has surfaced as a sole mean of pedagogic delivery. Nowadays, it is indispensable for all the academicians to adopt the e-learning approach, who earlier dealt with it with varying degrees of enthusiasm and concern.